CLASSIFIQUI: a Game for Software Requirements Classification Learning - Monteiro, Francisco Elenilson Pessoa; Carvalho, Rainara Maia; Gonçalves, Enyo José Tavares (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
Many problems in software development happen due to missing or insufficient handling of software requirements. The area that deals with how professionals must discover, document and validate requirements is Requirements Engineering (RE). RE is concerned with eliciting, analyzing, specifying, validating and managing user needs to be met by the software. In elicitation, professionals must discover and understand what are the customers and users needs. In this phase, a lot of information is passed on to the analysts and normally this information does not come in a succinct, complete and well-organized list. Serious games have been used to support several areas of computing knowledge, including RE. However, there is still a gap to support teaching requirements classification through play. Thus, this work presents the CLASSIFIQUI game, which was proposed to support the teaching of requirements classification. The game was evaluated through a study and proved to be suitable for teaching requirements classification.